Peningkatan Kompetensi Guru SLB Negeri Bugih Pamekasan Melalui Pemanfaatan Media Pembelajaran dan Aplikasi Belajar Online - Shefa Dwijayanti Ramadani; Agus Budiyono; Masdukil Makruf (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2021)
The conditions of the Covid-19 pandemic caused extraordinary changes in various sectors of life, including in the education sector. The closure of all school institutions